2012
DOI: 10.1177/0148607111416482
|View full text |Cite
|
Sign up to set email alerts
|

Prophylactic Anticoagulation Decreases Catheter‐Related Thrombosis and Occlusion in Children With Home Parenteral Nutrition

Abstract: Thromboprophylaxis significantly decreased catheter-related thrombosis and occlusion in children with PN without complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
2
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 23 publications
1
32
2
3
Order By: Relevance
“…Schoot et al [112] reviewed three randomized controlled trials and three controlled clinical trials of systemic treatment (low molecular weight heparin, antithrombin supplementation or low dose warfarin) and found no significant effects compared with no intervention in preventing venous thromboembolic events in pediatric cancer patients with tunneled CVC, and no differences in adverse events. In an investigation of the role of prophylactic anticoagulation in children receiving home PN, Vegting et al [113] compared outcomes with retrospective data from a time when their patients did not receive this treatment. Sixteen children received low molecular weight heparin (nadoparin) and two vitamin K antagonists.…”
Section: Interventions To Decrease Thrombotic Complications and Cvc Omentioning
confidence: 99%
“…Schoot et al [112] reviewed three randomized controlled trials and three controlled clinical trials of systemic treatment (low molecular weight heparin, antithrombin supplementation or low dose warfarin) and found no significant effects compared with no intervention in preventing venous thromboembolic events in pediatric cancer patients with tunneled CVC, and no differences in adverse events. In an investigation of the role of prophylactic anticoagulation in children receiving home PN, Vegting et al [113] compared outcomes with retrospective data from a time when their patients did not receive this treatment. Sixteen children received low molecular weight heparin (nadoparin) and two vitamin K antagonists.…”
Section: Interventions To Decrease Thrombotic Complications and Cvc Omentioning
confidence: 99%
“…41 There is, therefore, no evidence to support the routine use of chemical TP in children with indwelling CVCs, although VKA therapy may be useful in children requiring long-term central venous access for the administration of TPN. 12,23,42 Evidence for the efficacy of chemical TP in adolescents and children with trauma is limited. A study of 260,078 pediatric trauma patients between 2001 and 2008 showed that prescriptions of enoxaparin for TP doubled over the studied time period but without a change in the incidence of VTE, which remained at around 0.25%.…”
Section: Chemical Thromboprophylaxismentioning
confidence: 99%
“…From a clinical point of view, our data make it unlikely that platelet aggregation is involved in catheter-related thrombosis during parenteral nutrition [23]. Anticoagulation rather than platelet aggregation inhibitors may, therefore, be useful to prevent catheter-related thrombosis [32].…”
Section: Discussionmentioning
confidence: 87%